Pandemics, public health, and the regulation of borders : lessons from Covid-19 - Flood, Colleen M. (Routledge, 2024)
"This book examines how the COVID-19 pandemic has engendered a new and challenging environment in which borders drawn around people, places, and social structures have hardened, and new ones have emerged. Over the course of the COVID-19 pandemic, borders closed or became unwelcoming at the international, national, sub-national and local levels. Debate persists as to whether those countries and territories that tightly managed their borders, like New Zealand, Australia or Hong Kong, got it 'right' compared to those that did not. Without doubt, a majority of those who suffered and died throughout the pandemic have been those from vulnerable populations. Yet, on the other hand, efforts taken to manage the spread of the disease, such as through border management, have also disproportionately affected those who are most vulnerable. How, then is the right balance to be struck, acknowledging too the economic and other imperatives that may dissuade governments from taking public health steps? This book considers how international organizations, countries, and institutions within those countries should conceive of, and manage, borders as the world continues to struggle with COVID-19 and prepares for the next pandemic. Engaging a range of international, and subnational, examples, the book thematises the main issues at stake in the control and management of borders in the interests of public health. This book will be of considerable interest to academics in the fields of health law, anthropology, economics, history, medicine, public health, and political science, as well as policy makers and public health planners at national and subnational levels"-- Provided by publisher.
Keywords: COVID-19 (Disease) -- Law and legislation.; COVID-19 Pandemic, 2020-; Public health laws.; Border crossing.; Pandémie de COVID-19, 2020-; Passage de frontière.; Border crossing; COVID-19 (Disease) -- Law and legislation; Public health laws; LAW / Health; MEDICAL / Public Health; Since 2020